Triglyceride-glucose index in the prediction of acute kidney injury in patients undergoing coronary artery bypass surgery - Li, Chen; Lv, Xingping; Shen, Yezhou; Zhou, Wei; Shen, Tuo; Fan, Guoliang; Zhu, Feng (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe triglyceride-glucose (TyG) index, indicative of insulin resistance, is recognized for predicting cardiovascular disease and metabolic disorders, notably kidney disease. In coronary artery bypass grafting (CABG) surgery, its association with postoperative renal injury is significant, suggesting its potential as a predictor for acute kidney injury (AKI) in these patients.MethodsThis single-center, retrospective study included 296 patients. Patients were divided into AKI and non-AKI groups postoperatively according to the KDIGO grading criteria. Multiple linear regression was employed to identify factors influencing the TyG index. Logistic regression was utilized to examine the TyG index's association with AKI in CABG patients. The TyG index's predictive power for postoperative AKI was assessed using receiver operating characteristic (ROC) curve analysis. Assessment of the Predictive Performance of the Prediction Model via Calibration plot and Clinical Decision Curve Analysis.ResultsIn comparison between the AKI group and the non- AKI group post-CABG surgery, there was statistically significant differences in TyG index [7.53 [7.25, 7.95] vs. 6.99 [6.64, 7.39], P < 0.05]. Logistic regression analysis indicated that for each unit increase in the TyG index, the odds of developing acute kidney injury post-CABG surgery increased by 30.573 times [odds ratio (OR) = 30.573, 95% confidence interval (CI) 3.930–237.807, P < 0.001]. The area under the curve (AUC) for the TyG index in predicting postoperative AKI in CABG patients was 0.802 (P < 0.001; 95% CI: 0.753–0.851). The calibration plot of the model closely approximated the ideal diagonal line, and the clinical decision curve analysis demonstrated favorable clinical applicability.ConclusionElevated levels of the TyG index are closely associated with the occurrence of AKI in patients following CABG surgery, and the TyG index is a potential indicator for the development of AKI post-CABG.